Websights [domain name registration]. - Cherry, S.M (IEEE spectrum)
With the top-level .com name space now as overcrowded as many US telephone area codes, a set of long-standing disputes for control over top-level domains has erupted into open conflict. Several companies are going off on their own, assigning, for a fee, Internet addresses. The author describes how the problem is that addresses are not being coordinated Internetwide. The result is that the Internet could become something less than global. Some addresses will be recognized by only part of the Internet; other users will receive error messages such as ?domain not found?. Worse, the potential exists for two companies to use the same domain name, which could result in more confusion